2022
DOI: 10.1073/pnas.2117938119
|View full text |Cite
|
Sign up to set email alerts
|

Protein and lipid mass concentration measurement in tissues by stimulated Raman scattering microscopy

Abstract: Significance We report a quantitative Raman microscopy method that measures the concentration of protein and lipid in cells at high spatial resolution in living and in fixed samples of tissues, allowing quantitative studies of cell size and organelle regulation both in cell culture and in tissue slices; it can be applied to problems of cell size control, intracellular crowding, and lipid metabolism in the context of cell growth, cell differentiation, cell senescence, and pathology.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(87 citation statements)
references
References 70 publications
6
81
0
Order By: Relevance
“…SRS imaging at three Raman bands can separate the contribution of proteins and lipids, at the expense of increased computational complexity and imaging throughput. 34 The second complicating factor is lipid droplets. Lipid droplets are dynamic organelles that store neutral lipids.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…SRS imaging at three Raman bands can separate the contribution of proteins and lipids, at the expense of increased computational complexity and imaging throughput. 34 The second complicating factor is lipid droplets. Lipid droplets are dynamic organelles that store neutral lipids.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…31−33 By unmixing the contribution of lipids, proteins, and water, we showed that SRS imaging at three Raman bands (2853, 2935, and 3420 cm −1 , corresponding to CH 3 , CH 2 , and H 2 O Raman bands, respectively) can be used to map the density of lipids and proteins in cells. 34 Importantly, the use of water SRS signal to normalize signal loss due to the ubiquitous presence of sample-induced aberration and light scattering allowed quantitative density imaging in multicellular samples and tissues. 35,36 However, a major drawback of this method is that wavelength tuning is required, and as a result, the measurement speed is very slow, on the order of minutes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Stimulated Raman scattering (SRS) microscopy has demonstrated advantages of non-destructive 3D imaging with subcellular resolution in a label-free manner 7,8 . Recent work has even demonstrated quantitative mass concentration measurements of lipids, proteins, and water 9 . For label-free SRS imaging microscopy, the chemical specificity is achieved through hyperspectral imaging (HSI) or training of a deep learning model 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, quantitative phase imaging (QPI) techniques have been employed for imaging and analyzing the dynamics of biological organisms owing to their label-free and quantitative imaging capabilities [4][5][6][7][8][9]. QPI uses the refractive index (RI) distribution of a sample as an intrinsic imaging contrast and enables three-dimensional (3D) imaging of live unlabeled biological samples [10][11][12][13]. However, unlike thin biological cells or microorganisms [11,12,14,15], the large sizes and high RI values of nematodes result in technical challenges for QPI.…”
Section: Introductionmentioning
confidence: 99%
“…QPI uses the refractive index (RI) distribution of a sample as an intrinsic imaging contrast and enables three-dimensional (3D) imaging of live unlabeled biological samples [10][11][12][13]. However, unlike thin biological cells or microorganisms [11,12,14,15], the large sizes and high RI values of nematodes result in technical challenges for QPI. Large optical phase delay variations in nematodes generate significant phase-wrapping issues, deteriorating the imaging quality of 2D QPI techniques.…”
Section: Introductionmentioning
confidence: 99%